Application of PI-FBG sensor for humidity measurement in unsaturated soils - Guo, Jun-Yi; Shi, Bin; Sun, Meng-Ya; Cheng, Wei; Zhang, Cheng-Cheng; Wei, Guang-Qing; Wang, Xing (Measurement : journal of the International Measurement Confederation, 2022)
•The PI-FBG humidity sensor suitable for use in unsaturated soils was developed.•The encapsulated PI-FBG sensor performed well in ten different sand-kaolin mixtures.•The function between water content and humidity in unsaturated soils was established.•The influence of kaolin content on pore gas relative humidity was discussed. In this paper, the polyimide-coated fiber Bragg grating (PI-FBG) humidity sensor suitable for use in unsaturated soils was developed. Through a series of laboratory tests, the pore gas relative humidity in different sand-kaolin mixtures were measured and analyzed to verify the feasibility of the sensor in unsaturated soils. The results shows that the pore gas relative humidity in unsaturated soils first increases rapidly and then tends to be stable with the increase of water content. The relationship between them can be fitted by quadratic function when the pore gas relative humidity is less than 100%. In addition, the critical water content (w100%RH) of mixed soils increases linearly with the increase of kaolin content; when the water contents of mixed soils are same, higher kaolin content induces higher pore gas relative humidity.